A Framework to Assess the Influence of Different Cardiac Fibrosis Phenotypes and Border Zone on Arrhythmogenesis - Couto, Guilherme M.; Campos, Joventido O.; Santos, Rodrigo W. dos (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à Saúde, 2026)
Current computational models often oversimplify cardiac fibrosis, lacking micro-architecture details. To address this, we present a scalable computational pipeline extending a histologically-calibrated Perlin noise generator to automatically construct focal fibrotic cores and functional border zones. Using this framework, we conducted preliminary 2D electrophysiological simulations under localized hypoxia to evaluate four distinct phenotypes. Initial results suggest that phenotype influences tissue vulnerability, with diffuse architectures exhibiting a higher incidence of reentries under the tested conditions. Furthermore, the framework successfully models geometrically constrained lesions, highlighting that variations in the total diseased area between global and focal models substantially alter the number of arrhythmic events. This work underscores the importance of incorporating spatial heterogeneity and appropriate boundary constraints in predictive computational modeling.